Effect of Hot Induction Bending Followed by Controlled Heat Treatment on the Mechanical and Microstructural Behavior of API 5L X65 Carbon Steel Pipes - Hasibuan, Fardin; Yosua Luis Vigo Sitompul, Yosua Luis Vigo; Hakim, Arif Rahman; Sitio, Joni Mart (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
This study examines the mechanical and microstructural behavior of API 5L X65QS/QO PSL2 seamless carbon steel pipes subjected to a hot induction bending process followed by quenching and tempering. The research aimed to evaluate the combined effect of mechanical deformation and heat treatment on the material’s strength, hardness, and toughness. Experimental procedures were performed on a 12-inch seamless pipe bent at 900 ± 15 °C, quenched in agitated water at 15 °C, and tempered at 660 ± 15 °C. Mechanical testing revealed that the Ultimate Tensile Strength (UTS) and Yield Strength (YS) increased by approximately 8.5%, while hardness decreased slightly from 215 HV to 210 HV. Elongation improved from 29% to 32%, indicating enhanced ductility. Microstructural analysis showed a fine ferrite–pearlite structure with an ASTM grain size number greater than 8, confirming effective grain refinement achieved through controlled heat treatment. Overall, the combined hot induction bending, quenching, and tempering processes successfully produced a fine-grained material with improved strength, ductility, and toughness, demonstrating its suitability for high-performance and high-pressure pipeline applications.